Kepemilikan Institusional, Kinerja Perusahaan, dan Efek Moderasi dari Kepemilikan Institusional Aktif - Setiawan, Rahmat; Syarif, Moh Maulidi (UNUSA Press, 2019)
This research investigate impact of institutional ownership on firm performance, and moderating effect of active institutional ownership. Using purposive sampling and the period of 2012-2016, we obtained 436 observations of 99 manufacturing firms for dependent variable mea- sured by ROA, and 415 observations of 95 manufacturing firms for dependent variable measured by Tobin’s Q. We found that institutional ownership had significant positive effect on firm perfor- mance. Active institutional ownership as a moderating variable, strengthens the positive effect of institutional ownership on firm performance.